The unique chemistry of thiuram polysulfides enables energy dense lithium batteries. Issue 47 (23rd November 2017) - Bhargav, Amruth; Ma, Ying; Shashikala, Kollur; Cui, Yi; Losovyj, Yaroslav; Fu, Yongzhu
Abstract : Thiuram-type organopolysulfides show three discharge plateaus and high material utilization (up to 97%) throughout cycling. The mesomeric form of lithium pentamethylene dithiocarbamate with a positive nitrogen center, formed in the discharge, can act as polysulfide and sulfide anchors through strong coulombic interactions thus enabling long cycle life. Abstract : Organosulfur compounds are cheap and abundant cathode materials that can offer high specific energies. Herein, we explore for the first time, the common vulcanization accelerators viz. thiuram polysulfides embedded in carbon nanotubes as binder-free cathodes in lithium batteries that show 3 highly reversible redox reactions (3 discharge plateaus) and high material utilization (up to 97%). We use electrochemical characterization techniques, first-principles calculations, XPS, XRD, FTIR, and SEM to gain insight into the chemical transformations occurring during battery cycling. We identify that the mesomeric form of lithium pentamethylene dithiocarbamate with a positive nitrogen center, formed in the discharge, can act as polysulfide and sulfide anchors through strong coulombic interactions thus enabling a capacity retention of 87% after 100 cycles at C/5 rate. A high loading cathode with an areal capacity of 5.3 mA h cm −2 tested under a low electrolyte to active material ratio of 3 μL mg −1 yields an active material specific energy of 1156 W h kg −1 thus demonstrating the potential of this class of compounds in high specific energy lithium batteries.